2013
DOI: 10.1056/nejmoa1306220
|View full text |Cite
|
Sign up to set email alerts
|

Targeting BTK with Ibrutinib in Relapsed or Refractory Mantle-Cell Lymphoma

Abstract: BACKGROUND Bruton's tyrosine kinase (BTK) is a mediator of the B-cell–receptor signaling pathway implicated in the pathogenesis of B-cell cancers. In a phase 1 study, ibrutinib, a BTK inhibitor, showed antitumor activity in several types of non-Hodgkin's lymphoma, including mantle-cell lymphoma. METHODS In this phase 2 study, we investigated oral ibrutinib, at a daily dose of 560 mg, in 111 patients with relapsed or refractory mantle-cell lymphoma. Patients were enrolled into two groups: those who had previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

38
1,164
5
25

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,488 publications
(1,260 citation statements)
references
References 30 publications
38
1,164
5
25
Order By: Relevance
“…The U.S. Food and Drug Administration declared ibrutinib as a breakthrough therapy in February 2013 for the treatment of relapsed/ refractory mantle cell lymphoma and gave approval for this indication in November 2013 (Wang et al, 2013). Recently, in February 2014 the Food and Drug Administration provided accelerated approval for ibrutinib for chronic lymphocytic leukemia in patients who had received at least one previous therapy (Byrd et al, 2013;O'Brien et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The U.S. Food and Drug Administration declared ibrutinib as a breakthrough therapy in February 2013 for the treatment of relapsed/ refractory mantle cell lymphoma and gave approval for this indication in November 2013 (Wang et al, 2013). Recently, in February 2014 the Food and Drug Administration provided accelerated approval for ibrutinib for chronic lymphocytic leukemia in patients who had received at least one previous therapy (Byrd et al, 2013;O'Brien et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most events were grade 1 to 2 (spontaneous bruising or petechiae), but in 5% of patients, they were of grade 3 or higher after trauma. [4][5][6] Platelets are the most important blood cells to prevent bleeding after vascular injury. Two Tec family kinases, Btk and Tec, are involved in platelet activation downstream of the collagen receptor glycoprotein VI (GPVI) via phospholipase Cg2 (PLCg2) phosphorylation and activation.…”
mentioning
confidence: 99%
“…Ibrutinib (previously called PCI-32765) is a potent (IC 50 , 0.5 nM) BTK inhibitor that inactivates BTK through irreversible covalent bonding to Cys-481 in the ATP-binding domain of BTK (3)(4)(5). Early-stage clinical trials found ibrutinib to be particularly active in patients with CLL (6, 7) and mantle cell lymphoma (8), and the drug recently has been Food and Drug Administration-approved for patients with relapsed CLL and mantle cell lymphoma.…”
mentioning
confidence: 99%